1988
DOI: 10.1177/000992288802700104
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Hemorrhage in Small-for-gestational-age Neonates: Comparison With Weight-matched Appropriate-for-gestational-age Infants

Abstract: In a comparative study of 93 small-for-gestational-age (SGA) infants against 93 weight-matched, appropriate-for-gestational-age (AGA) neonates, the SGA group exhibited a significantly lower incidence of periventricular-intraventricular type intracranial hemorrhage (ICH) at the first ultrasound scan than did the AGA neonates (9/93 vs 21/93; p less than 0.02). This apparent advantage was no longer maintained in later scans of the first week (16/93 vs 27/93; NS), despite the fact that the SGA group were 4 weeks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Several studies have found a decrease in the morbidity associated with prematurity when the infants are also poorly grown, suggesting an advantage to the stress of poor growth. [1][2][3] Others 4 found increased respiratory morbidity. A number of studies have confirmed that mortality in preterm growth-restricted infants is higher when compared to normally grown infants of the same gestational age.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found a decrease in the morbidity associated with prematurity when the infants are also poorly grown, suggesting an advantage to the stress of poor growth. [1][2][3] Others 4 found increased respiratory morbidity. A number of studies have confirmed that mortality in preterm growth-restricted infants is higher when compared to normally grown infants of the same gestational age.…”
Section: Introductionmentioning
confidence: 99%
“…Small‐for‐gestational‐age (SGA) neonates have clinical problems linked to intrauterine hypoxia and decreased subcutaneous fat tissue. Some of the common issues in these newborns include hypoxic‐ischemic encephalopathy; intraventricular hemorrhage; periventricular leukomalacia (Dincsoy et al. , 1988; Doctor et al.…”
Section: Introductionmentioning
confidence: 99%
“…Small-for-gestational-age (SGA) neonates have clinical problems linked to intrauterine hypoxia and decreased subcutaneous fat tissue. Some of the common issues in these newborns include hypoxic-ischemic encephalopathy; intraventricular hemorrhage; periventricular leukomalacia (Dincsoy et al, 1988;Doctor et al, 2001;Taeusch, Ballard & Gleason, 2005); respiratory distress syndrome; pulmonary hypertension; hemorrhagic pulmonary edema; meconium aspiration syndrome (Taeusch et al, 2005); metabolic disorders such as hypoglycemia, hyperglycemia, and hypocalcemia Bhat et al, 2000); mesenteric ischemia; necrotizing enterocolitis (Hakanson & Oh, 1977), and thermoregulatory disorders (Taeusch et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Three previous studies found no association between AHT and IVH [7,13,25] , while other studies showed borderline-significant association [12,26] and three studies showed some significant association [5,6,16,24] . The above-mentioned studies vary considerably in the methodology, study populations, definitions, variables assessed, etc.…”
Section: Discussionmentioning
confidence: 97%
“…In preterm infants ! 26 weeks' gestation, AHT occurs more after cesarean delivery (48%) than after vaginal delivery (33%) [11] and more in SGA than in appropriate-for-gestational-age preterm infants [12] . Recent guidelines for resuscitation of premature infants in the delivery room, published by the American Heart Association and American Academy of Pediatrics in 2006 and by other investigators [10,[13][14][15] , have suggested the use of polyethylene wraps or chemical warming mattresses in order to prevent heat loss in verypreterm infants immediately after birth.…”
mentioning
confidence: 99%